Contribuições críticas para os processos de ensino e aprendizagem: experiências de alunos em um projeto de extensão sobre pesca responsável na Costa Rica - Calvo González, Isabel (Universidad Nacional del Litoral, 2020)
This article exposes the systematization of the perceptions of the students of the Economic and Social Planning career linked to the project of Extension "Community Management for the productive strengthening of the Marine Areas of Responsible Fishing of Golfo de Nicoya", it is tried to know the form in which the curricularization of the university extension offers contributions in the transformation of the processes of teaching and learning from the critical reconstruction of the experiences of the student body. Methodologically, the work is based on the discovery and subjective/ intersubjective interpretation of reality, which implies a dialectical–materialistic approach. We used as instruments the conversational interview and the realization of participative workshops. From the application of the instruments, four analytical categories were constructed, which allowed demonstrating that the students, by means of the social participative accompaniment to local groups, have deconstructions on traditional learning and that from their experience they construct new forms when establishing spaces of dialogue and horizontal relations with the people of the communities, strengthening their professional training.